PEMBERDAYAAN SISWA SEKOLAH DASAR DALAM PENCEGAHAN BULLYING MELALUI EDUKASI DAN MEDIA PROMOSI KESEHATAN DI SDN 11 KURAO PAGANG KOTA PADANG - Syafrawati syafrawati; Sri Siswati; Annisa Afritika (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Bullying remains a common issue in elementary schools, posing serious threats to students' mental, social, and academic development. SDN 11 Kurao Pagang, located in Nanggalo District, Padang, is one such school facing this challenge. Its close proximity to a junior high school raises concerns, as interactions between the two student groups may expose younger students to inappropriate behaviors, including bullying. This community service program aimed to enhance students’ knowledge and awareness of bullying and its prevention. The intervention involved interactive educational sessions through lectures, discussions, pre- and post-tests, and the distribution of health promotion materials such as posters and pocket books. The content was delivered using visually engaging PowerPoint slides tailored to the comprehension level of elementary students. The results showed a significant improvement in students’ understanding of bullying, with the average test score rising from 71.25 (pre-test) to 85.42 (post-test). These findings indicate that the program was effective in increasing students' knowledge about the definition, types, impacts, and prevention of bullying. In addition, the activity contributed to fostering a more positive and safer school environment. Regular implementation of similar programs is recommended to reinforce these outcomes and ensure the long-term sustainability of their positive impact.